2016
DOI: 10.3390/jmse4040072
|View full text |Cite
|
Sign up to set email alerts
|

Improvements for the Western North Atlantic, Caribbean and Gulf of Mexico ADCIRC Tidal Database (EC2015)

Abstract: This research details the development and validation of an updated constituent tidal database for the Western North Atlantic, Caribbean and Gulf of Mexico (WNAT) region, referred to as the EC2015 database. Regional databases, such as EC2015, provide much higher resolution than global databases allowing users to more accurately define the tidal forcing on smaller sub-region domains. The database last underwent major updates in 2001 and was developed using the two-dimensional, depth-integrated form of the coasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…The methodology of this study closely follows that used for the development of the EC2015 tidal database for the eastern coast of the United States [26]; therefore, the entire outline and much of the text provided in Section 2.1, Section 2.2, and Section 2.3 is similar to that of our previous study (in order that this paper is complete enough to stand alone for those readers who are not familiar with that study). While the methodology is similar, it is not the same, due to peculiarities of local regions, so readers are cautioned not to skip these sections entirely.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The methodology of this study closely follows that used for the development of the EC2015 tidal database for the eastern coast of the United States [26]; therefore, the entire outline and much of the text provided in Section 2.1, Section 2.2, and Section 2.3 is similar to that of our previous study (in order that this paper is complete enough to stand alone for those readers who are not familiar with that study). While the methodology is similar, it is not the same, due to peculiarities of local regions, so readers are cautioned not to skip these sections entirely.…”
Section: Methodsmentioning
confidence: 99%
“…Further tests on the ENPAC03 model domain revealed that the presence of the shelf break across the open ocean boundary to the west prevented stable runs when ADCIRC's advective terms were enabled for use (this was confirmed upon examination of the ENPAC03 report as well [27]). Experience gained while updating the Western North Atlantic ADCIRC tidal constituent database revealed that the advective terms played an important role in reducing errors in the shallow near-shore regions [26]. In order to avoid the S2 amphidrome off the Aleutian Islands, an attempt was made to extend the ENPAC03 domain just west of the shelf near longitude −180 • .…”
Section: Model Input Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…The Advanced Circulation (ADCIRC [50]) model serves as the hydrodynamic model in the STORM-CoRe coupled model system. ADCIRC, which has been in use for over 35 years, has seen a wide variety of applications, which include flood inundation maps for coastal areas [51,52], modeling baroclinic driven circulation [53], real-time prediction of storm surge to provide guidance [13,21], surge and riverine flooding [14,[54][55][56], modeling tides and wind driven circulation [57,58] and an integrated, scenario-based evacuation and sheltering system [56,59]. The ADCIRC model employs the shallow water equations in their non-linear formulation, subject to hydrostatic and Boussinesq approximations.…”
Section: Hydrodynamic Model Adcircmentioning
confidence: 99%